Incomplete insurance and open-economy spillovers of labor market reforms - Brigitte Hochmuth; Christian Merkl; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2024)
This paper shows that less generous unemployment benefits in one country may generate substantial negative long-run consumption spillovers to non-reforming countries under incomplete consumption insurance. While lower benefits reduce unemployment in the reforming country, employed workers increase their precautionary savings to compensate for reduced government-provided insurance. A portion of these additional savings flows to the non-reforming country and depresses long-term consumption due to the negative net foreign asset position. To discipline our quantitative model, we estimate the increase of Germany's tradable sector in the aftermath of the Hartz unemployment insurance reform based on firm-level data. Our quantitative model matches a significant fraction of various macroeconomic trends after the reform, namely Germany's persistent increase of aggregate savings and net foreign assets, the increase of net exports, the real exchange rate depreciation within the Eurozone, and the decline in unemployment. Conversely, Germany's wage moderation before the reform appears to be unrelated to most of these phenomena.
Keywords: E21; E24; F16; F41; 330; Unemployment insurance reform; spillover effects; precautionary savings